Specific microbiota enhances intestinal IgA levels by inducing TGF‐β in T follicular helper cells of Peyer's patches in mice. Issue 6 (27th February 2020) - Beller, Alexander; Kruglov, Andrey; Durek, Pawel; von Goetze, Victoria; Werner, Katharina; Heinz, Gitta Anne; Ninnemann, Justus; Lehmann, Katrin; Maier, René; Hoffmann, Ute; Riedel, René; Heiking, Kevin; et al.
Abstract: In humans and mice, mucosal immune responses are dominated by IgA antibodies and the cytokine TGF‐β, suppressing unwanted immune reactions but also targeting Ig class switching to IgA. It had been suggested that eosinophils promote the generation and maintenance of mucosal IgA‐expressing plasma cells. Here, we demonstrate that not eosinophils, but specific bacteria determine mucosal IgA production. Co‐housing of eosinophil‐deficient mice with mice having high intestinal IgA levels, as well as the intentional microbiota transfer induces TGF‐β expression in intestinal T follicular helper cells, thereby promoting IgA class switching in Peyer's patches, enhancing IgA + plasma cell numbers in the small intestinal lamina propria and levels of mucosal IgA. We show that bacteria highly enriched for the genus Anaeroplasma are sufficient to induce these changes and enhance IgA levels when adoptively transferred. Thus, specific members of the intestinal microbiota and not the microbiota as such regulate gut homeostasis, by promoting the expression of immune‐regulatory TGF‐β and of mucosal IgA. Abstract : Microbiota containing Anaeroplasma enhances TGF‐β expression in Tfh cells of the PP. This leads to the increased class switch to IgA during GC reaction, resulting in enhanced numbers of IgA + plasma cells and fecal IgA levels.